2009
DOI: 10.1364/oe.17.005794
|View full text |Cite
|
Sign up to set email alerts
|

Retention of polarization signatures in SHG microscopy of scattering tissues through optical clearing

Abstract: Polarization responses in Second Harmonic Generation (SHG) imaging microscopy are a valuable method to quantify aspects of tissue structure, and may be a means to differentiate normal and diseased tissues. Due to multiple scattering, the polarization data is lost in turbid tissues. Here we investigate if this information can be retained through the use of optical clearing which greatly reduces the scattering coefficient and increases the corresponding mean free path. To this end, we have measured the SHG inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 35 publications
(58 reference statements)
1
71
0
Order By: Relevance
“…Optical clearing of the mouse tail tendon in vitro exposed to the glycerol solutions with different concentration was demonstrated in the papers by LaComb et al [72], Nadiarnykh and Campagnola [73], and Rylander et al [31]. The authors managed to increase the probing depth in the second harmonic generation microscopy up to 450 µm at the expense of considerable reduction of the scattering coefficient (up to 130 folds at the wavelength 890 nm during 5 hours) and increasing the packaging density of fibrils (according to the data of electron microscopy, the volume fraction of fibrils increased from 0.65 to 0.9) [31].…”
Section: Immersion Clearingmentioning
confidence: 92%
See 1 more Smart Citation
“…Optical clearing of the mouse tail tendon in vitro exposed to the glycerol solutions with different concentration was demonstrated in the papers by LaComb et al [72], Nadiarnykh and Campagnola [73], and Rylander et al [31]. The authors managed to increase the probing depth in the second harmonic generation microscopy up to 450 µm at the expense of considerable reduction of the scattering coefficient (up to 130 folds at the wavelength 890 nm during 5 hours) and increasing the packaging density of fibrils (according to the data of electron microscopy, the volume fraction of fibrils increased from 0.65 to 0.9) [31].…”
Section: Immersion Clearingmentioning
confidence: 92%
“…New original results obtained using the combination of optical clearing with the known optical visualisation methods, such as laser speckle-contrast imaging [34, 71,75,77,79], OCT [20,29,35,[59][60][61]65,69,80,82], microscopic imaging [23,24,83,84], ultra-microscopy [85][86][87], etc., demonstrated high potentiality of their mutual use not only for getting high-resolution structure and functional tissue images in vitro [72,73,[83][84][85][86][87], but also for optical imaging and diagnostics in vivo [25,34,45,50,59,61,65,68,70,71,[75][76][77][79][80][81]. Table 1 shows the increase of the light penetration depth, caused by clearing agents in some diagnostic methods.…”
Section: Immersion Clearingmentioning
confidence: 99%
“…As polarization is scrambled in scattering tissues [31], the tissues were optically cleared in 50% glycerol/PBS overnight [31]. Giant unilamellar vesicles (GUVs) were created from L-aPhosphatidylcholine lipid (Avanti Polar Lipids) for circular polarization calibration.…”
Section: Sample Preparationmentioning
confidence: 99%
“…As the tendon is sufficiently thick to support multiple scattering events which randomize the polarization response, the specimen must be first optically cleared to reduce the scattering and increase the transparency [31]. Here we define 0° condition as where the laser polarization is aligned with the long axis of a collagen fiber(s).…”
Section: Shg Imaging Of Rat Tail Tendonmentioning
confidence: 99%
“…3, 4, 11-17 and recent ones present optical clearing of tissues such as skin, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sclera, [33][34][35] and skeletal muscle. [36][37][38][39][40][41] We have found that only in two papers optical clearing of heart tissues were investigated. 42,43 Authors of Ref.…”
Section: Introductionmentioning
confidence: 99%